2004
DOI: 10.1016/j.trstmh.2003.12.005
|View full text |Cite
|
Sign up to set email alerts
|

The effect of single dose ivermectin alone or in combination with albendazole on Wuchereria bancrofti infection in primary school children in Tanzania

Abstract: Examination of 1829 children from 6 primary schools in coastal Tanzania revealed overall Wuchereria bancrofti microfilaria (mf) and circulating filarial antigen (CFA) prevalences of 17.3% and 43.7%, respectively. A randomized double-blind field trial with a single dose of ivermectin (150-200 microg/kg body weight) alone or in combination with albendazole (400 mg) was subsequently carried out among these children. Both treatment regimens resulted in a considerable decrease in mean mf intensities, with overall r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 29 publications
2
64
1
Order By: Relevance
“…Thus, although the mean intensity of both indices had decreased to about half of the pre-MDA level at the end of the study in October 2008, there was no clear effect on the prevalences. Previous studies have similarly indicated a limited effect of the ivermectin/albendazole combination on circulating filarial antigenemia [10], [21], in agreement with the general understanding that ivermectin is mainly a microfilaricidal drug. The limited reduction in level of antibodies to Bm14 concurs with the observed remaining infection burden and continued transmission of LF in the study community.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Thus, although the mean intensity of both indices had decreased to about half of the pre-MDA level at the end of the study in October 2008, there was no clear effect on the prevalences. Previous studies have similarly indicated a limited effect of the ivermectin/albendazole combination on circulating filarial antigenemia [10], [21], in agreement with the general understanding that ivermectin is mainly a microfilaricidal drug. The limited reduction in level of antibodies to Bm14 concurs with the observed remaining infection burden and continued transmission of LF in the study community.…”
Section: Discussionsupporting
confidence: 83%
“…Early trials in selected mf positive individuals [17][19] as well as community based field trials [10], [20][22] demonstrated that this drug combination safely and effectively reduced W. bancrofti microfilaraemias, thus making it suitable for use in large scale transmission control [23]. Here we report on the effect of repeated MDAs with this drug combination in a highly LF endemic community of Tanzania, as applied by the NLFEP.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…[24-30]. Prior to start-up of the NLFEP-activities in Tanga Region in 2004, no control had taken place in any of the sites used in the present study.…”
Section: Discussionmentioning
confidence: 99%